SOSIALISASI PENTINGNYA PENDAFTARAN MEREK BAGI UMKM DI KOTA MEDAN - dahlia kusuma dewi; amelia alsa; Dahris Siregar; awaludin awaludin; andrio Bukit; Muhammad Citra Ramadhan; Irma Herliza Rizki; alvi syahrin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2022)
Since the Covid-19 pandemic, many new businesses have sprung up in the community, both in cities and in rural areas. These businesses have sprung up due to the number of people being laid off or being laid off, so many have opened businesses to meet their daily needs. From that business into an MSME. Micro, Small and Medium Enterprises (MSMEs) are businesses owned by individuals or business entities in which business actors produce their own products. These products need legal protection. However, the protection of circulating products is still weak. Therefore, the way people show the identity and uniqueness of the trade products they have, a trademark is created. In order to create a trademark to be better known in the community and avoid trade competition even though the type of product being cultivated is the same. However, there are several problems, namely that the mark must be registered first in order to get legal protection and secondly, the public does not understand where to register the mark and under what conditions. The method of activities carried out is by observation and socialization. The results of this service are known that there are still many people who do not know the importance of registering trademarks for their MSMEs, do not know how to register trademarks for MSMEs.